Practical Floating Capacitance Multiplier Implementation with Commercially Available IC LT1228s - Natchanai Roongmuanpha; Worapong Tangsrirat (My University, 2021)
A practical realization of a tunable floating capacitance multiplier using commercially available integrated circuits, namely LT1228 is proposed. The synthetic capacitor utilizes only two IC LT1228s along with two passive components (one resistor and one capacitor). The capacitance multiplication factor is electronically controllable through the transconductance gain of the LT1228. The effects of non-ideal transfer gains and parasitic elements of the LT1228 on the circuit performance have been evaluated in detail. The applicability of the proposed floating capacitance multiplier as a second-order band-pass filter is also presented. The claimed theory is verified by several PSPICE simulations and experimental test results.
Keywords: Parasitic capacitance; Transconductance; Radio Frequency Integrated Circuit Design